2011
DOI: 10.1039/c0sm01148g
|View full text |Cite
|
Sign up to set email alerts
|

Ferrocene based organometallic gelators: a supramolecular synthon approach

Abstract: The supramolecular synthon namely primary ammonium dicarboxylate (PAD) synthon has been exploited to generate a new series of salt based low molecular weight gelators (LMWGs) derived from ferrocenedicarboxylic acid (FDCA) and primary amines Me-(CH 2 ) n -NH 2 (n ¼ 3-15). While most of the salts are capable of forming gels with DMSO and DMF, nearly all of them show a tendency to form gels with at least one of the solvents studied. Structure property correlation based on single crystal and powder X-ray diffracti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 54 publications
2
29
0
Order By: Relevance
“…In the present work, we have deliberately chosen to synthesize PAD salts with n‐alkyl ammonium cations with varying alkyl chain length. This is because PAD salts usually displayed 2D supramolecular synthon . Under the influence of alkyl‐alkyl interactions, PAD salts also displayed 1D nanotubular supramolecular synthon leading to gelation .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the present work, we have deliberately chosen to synthesize PAD salts with n‐alkyl ammonium cations with varying alkyl chain length. This is because PAD salts usually displayed 2D supramolecular synthon . Under the influence of alkyl‐alkyl interactions, PAD salts also displayed 1D nanotubular supramolecular synthon leading to gelation .…”
Section: Resultsmentioning
confidence: 99%
“…This is because PADs alts usually displayed 2D supramolecular synthon. [67] Undert he influenceo fa lkyl-alkyl interactions, PADs altsa lso displayed 1D nanotubulars upramolecular synthon leading to gelation. [58] Therefore, it was utmost important to study the single crystal structures of the PADs alts studied herein.…”
Section: Single Crystal and Powder X-ray Diffraction Studiesmentioning
confidence: 99%
“…Although, there are a few reports on structure-property correlation of metallogels, [41][42][43][44][45] designing metallogels with specified properties and structure is still a daunting task. We have shown that metal binding to functionality such as a pyridyl group can 'switch on' gelation by removing the competing urea-pyridyl hydrogen bonding interaction.…”
Section: Methodsmentioning
confidence: 99%
“…This results in the substitution of divalent cations, which normally stabilize the surface membrane structures by linking adjacent negatively charged components. The found structure-property correlations were utilized to study micelles (Pires & El Seoud, 2006;Shimizu et al, 2003), thin films and gels (Sahoo et al, 2011(Sahoo et al, , 2009, ionic liquid crystals (Wei et al, 2011), biological membranes (Skočibušić et al, 2016) and binding modes in cancer radiotherapy (Saw et al, 2006). One of the most effective drugs belonging to the QAS family is benzyldimethyl{3-[(1-oxotetradecyl)amino]propyl}ammonium chloride monohydrate (MR) bearing the trade name Miramistin (Cook & Moss, 1949;Krivoshein et al, 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Single-crystal X-ray diffraction data for the amphiphilic molecules of QASs have already been used to model the behaviour of these systems in soft matter and at various interfaces. The found structure-property correlations were utilized to study micelles (Pires & El Seoud, 2006;Shimizu et al, 2003), thin films and gels (Sahoo et al, 2011(Sahoo et al, , 2009, ionic liquid crystals (Wei et al, 2011), biological membranes (Skočibušić et al, 2016) and binding modes in cancer radiotherapy (Saw et al, 2006).…”
Section: Introductionmentioning
confidence: 99%